Engineering reference manual - Larrañaga, Michael David (AIHA, 2012)
"A convenient reference summary of current, pertinent, practical information for OEHS professionals"--Cover.
Formerly the "Engineering field reference manual."
"A publication of the American Industrial Hygiene Association"--Cover.
Keywords: Industrial hygiene -- Handbooks, manuals, etc.; elektronické knihy; electronic books